2020
DOI: 10.1177/2055102920953049
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among newly admitted patients to cancer hospital in Vietnam and associated factors

Abstract: A cross-sectional study was conducted among 262 newly admitted patients of a cancer hospital in Vietnam. The Vietnamese version EORTC-30 questionnaire 3.0 was used to interviews patients during the first week after their admission. Lower global quality of life and physical functioning scores were significantly associated with older age, lung and gastrointestinal cancers. Emotional functioning score was lower among female patients as compared to males. Financial difficulty was an important preditor for almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These findings were consistent with the previous studies conducted in Vietnam or eight Southeast Asian countries (including Vietnam), which found poor economic situations or financial difficulties of cancer patients as predictors for impaired HRQOL. 37 , 43 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were consistent with the previous studies conducted in Vietnam or eight Southeast Asian countries (including Vietnam), which found poor economic situations or financial difficulties of cancer patients as predictors for impaired HRQOL. 37 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the previous studies conducted in Vietnam or eight Southeast Asian countries (including Vietnam), which found poor economic situations or financial difficulties of cancer patients as predictors for impaired HRQOL. 37,43 Besides the economic problems or concerns during the COVID-19 pandemic, gender and cancer sites were identified as the associated factors, but not cancer stage, in which more advanced stages have been associated with poorer QOL in previous studies. 44,45 The included patients could independently answer the questionnaire, suggesting that their health status could be similar between the advanced and early stages.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Another study among newly admitted cancer found that in the early stage of cancer, mental-related symptoms were more prevalent and mental health was affected more severely before the physical-related symptom manifests. 33 Therefore, education on how to cope with mental issues during treatment should be initiated early.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been some findings on the quality of life in this group of patients. 32 , 33 Understanding health literacy in newly admitted cancer patients, prior to treatment is important, especially in the context of a developing country like Vietnam, where the burden of non-communicable diseases like cancer has been increasing. From 1990 to 2018, the number of new cancer cases has tripled.…”
Section: Introductionmentioning
confidence: 99%